Political Economy at Any Speed: What Determines Traffic Citations? - Makowsky, Michael D; Stratmann, Thomas (American Economic Review, 2009)
Speeding tickets are determined not only by the speed of the offender, but also by incentives faced by police officers and their vote-maximizing principals. We hypothesize that police officers issue fines more frequently when drivers have a higher opportunity cost of contesting a ticket, and when drivers are not residents of the local municipality. We also predict that local officers are more likely to issue a ticket to out-of-town drivers when fiscal conditions are tight and legal limits prevent increases in property taxes. Using data from traffic stops in Massachusetts, we find support for our hypotheses. (JEL H76, R41)